Arctic PASSION Education & Training Plan ... - Lenz, Josefine; Grosfeld, Lisa; Heerema, Sabrina; Sinisalo, Anna (Zenodo, 2021)
The empowerment through education and capacity building of the next generation is a key aspect of Arctic PASSION. This Arctic PASSION Education and Training Plan conceptualises the education and training formats planned for the next four years: The Arctic PASSION School with two corresponding online workshops, and an online seminar and dialogue series. Arctic PASSION intends to reach out to the next generation impacted by the changing Arctic environment and applies the co-creational aspect of the whole project to the education activities. Key aspects such as the co-development and exchange of knowledge, inclusion and dialogue of different people, perspectives, career levels and backgrounds crosscut over all formats. The planned activities are mainly targeted to Indigenous and non-Indigenous early career scientists, as well as Arctic and Indigenous Youth. This plan also outlines their involvement in the Arctic PASSION project, by acting as Arctic PASSION Ambassadors and as representatives in the Arctic ...